1997
DOI: 10.1002/(sici)1096-8644(199709)104:1<47::aid-ajpa4>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Primate natal coats: A preliminary analysis of distribution and function

Abstract: Pelage coloration of infants was compiled for 138 species of primates. Three functional hypotheses--alloparental, infant defense, and paternity cloak--for primate natal coats are tested. Neonatal pelage contrasted with adult pelage in over half of the species examined. Subtle or inconspicuous contrast was more common than flamboyant contrast. Natal coats began to change at 5.7 weeks and disappeared by 18.0 weeks postpartum on average. The first body part to lose natal coloration was the head and/or dorsum in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 73 publications
2
70
1
1
Order By: Relevance
“…We used data on natal coat colors compiled by Treves (1997), who collated the information for 138 species of primates from two sources, a literature search and a survey questionnaire distributed to 40 zoological facilities, and then classified the species into three categories originally suggested by Hrdy (1976), as follows: category 0, natal coats that are indistinguishable from adult coats, referred to as ''no contrast'' (Treves 1997) or ''adult-like pelage'' (Hrdy 1976); category 1, natal coats that contrast with but are not strikingly different from adults (these coats may be either darker or paler than adult coats; Hrdy 1976); and category 2, flamboyant natal coats that are distinctive with bright contrasting coloration from adult coats (e.g., silvered leaf monkeys (Trachypithecus cristatus) are born with orange-colored coats, which are strikingly different from the silver to gray coats of adults; Bernstein 1968).…”
Section: Data Collection Of Carriage Patterns and Its Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used data on natal coat colors compiled by Treves (1997), who collated the information for 138 species of primates from two sources, a literature search and a survey questionnaire distributed to 40 zoological facilities, and then classified the species into three categories originally suggested by Hrdy (1976), as follows: category 0, natal coats that are indistinguishable from adult coats, referred to as ''no contrast'' (Treves 1997) or ''adult-like pelage'' (Hrdy 1976); category 1, natal coats that contrast with but are not strikingly different from adults (these coats may be either darker or paler than adult coats; Hrdy 1976); and category 2, flamboyant natal coats that are distinctive with bright contrasting coloration from adult coats (e.g., silvered leaf monkeys (Trachypithecus cristatus) are born with orange-colored coats, which are strikingly different from the silver to gray coats of adults; Bernstein 1968).…”
Section: Data Collection Of Carriage Patterns and Its Problemsmentioning
confidence: 99%
“…See Appendix for the sources b A aboreal, T terrestrial, T/A terrestrial and arboreal; sourced from Rowe (1996) c Most values were sourced from Treves (1997). See the text for values (0, 1 or 2).…”
Section: Colobine Monkeysmentioning
confidence: 99%
“…This mortality risk can be expected to select for the evolution of traits in infants that counter the threat of infanticide. For example, Treves (1997) has shown that natal coat contrast is significantly associated with adult testes weight, suggesting a link between mating system and infant colouration, and that the natal coats found in many species of primate may serve as an infanticide avoidance strategy.…”
Section: Sexual Selection and Infancymentioning
confidence: 99%
“…In primates, color changes can occur with sexual maturation, e.g., male gorillas (Gorilla gorilla) experience a silvering of the hair on the back indicative of adulthood, or some primate infants begin life with a conspicuous natal coat that becomes less dramatic with age, e.g., the orange coat of infant Silvered Leaf monkeys (Trachypithecus cristatus) [Alley, 1980;Treves, 1997;Bradley and Mundy, 2008]. Other bright and highly visible colors often occur on the bare-skinned areas of both males and females, e.g., the bright red sexual swellings of female Hamadryas baboons (Papio hamadryas) in estrus, the bright blue genitals of male Vervet monkeys (Chlorocebus pygerythrus), and the red-and blue-banded face of the male Mandrill (Mandrillus sphinx).…”
Section: Introductionmentioning
confidence: 99%